2015
DOI: 10.1093/ndt/gfv368
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evolution of post-transplant diabetes mellitus

Abstract: PTDM and prediabetes are very common in renal transplantation. Classic metabolic factors like obesity, prediabetes and insulin resistance promote the evolution of PTDM and prediabetes. Patients with normal glucose metabolism rarely develop PTDM. OGTT is necessary to detect PTDM and prediabetes and thus should be included in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
79
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 27 publications
11
79
1
1
Order By: Relevance
“…The present investigations now clearly demonstrate the dynamic nature of glucose metabolism after transplantation, questioning in particular the concept of reporting cumulative incidences in long-term follow-up after transplantation. Porrini and colleagues were the first to demonstrate the reversibility of prediabetes and PTDM in follow-up after kidney transplantation [18]. Our results are in line with and extend these findings, illustrating not only the overall evolution between months 3 and 36 but also the highly dynamic nature of glucose metabolism at sequential time points after kidney transplantation.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The present investigations now clearly demonstrate the dynamic nature of glucose metabolism after transplantation, questioning in particular the concept of reporting cumulative incidences in long-term follow-up after transplantation. Porrini and colleagues were the first to demonstrate the reversibility of prediabetes and PTDM in follow-up after kidney transplantation [18]. Our results are in line with and extend these findings, illustrating not only the overall evolution between months 3 and 36 but also the highly dynamic nature of glucose metabolism at sequential time points after kidney transplantation.…”
Section: Discussionsupporting
confidence: 90%
“…In kidney transplant recipients, within a similar period of observation, both Porrini et al and our data demonstrate substantial shifts from the prediabetic state towards both manifest diabetes and NGT. In comparison to the general population, the proportion of patients normalizing glucose metabolism (43%) is higher after transplantation [18]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent analysis of serial oGTTs in 672 KTRs over 5 years posttransplant, Porrini and colleagues reported similar outcomes. 26 In their prospective trial, 28% of patients showed oGTT results indicative of prediabetes and 21% of these patients developed late posttransplant diabetes mellitus during follow-up, similar to our result of approximately 16%. They reported a much higher prevalence of NODAT at 60 months after transplant, at 33.6%, versus 7.8% at about 120 months post transplant in our cohort.…”
Section: Discussionsupporting
confidence: 88%